Current Evidence on the Effect of Beetroot Juice During Exercise Efforts - He, Sun; Tengku-Kamalden, Tengku Fadilah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Some athletes consume supplements to improve the effect of training and achieve optimal performance during competition. Among the different supplements, beetroot juice has been indicative of improved nitric oxide (NO) concentration in blood, which can promote vasodilation, blood flow, gene expression, mitochondrial efficiency and gas exchange. Different methods have been proposed to classify beetroot juice as an egorgenic aid that can improve the performance of athletes. The objective of this paper is to review methods chosen to gain greater and detailed understanding regarding current issues about the effect of beetroot juice as an ergogenic aid during exercise efforts. Based on Pubmed database, conceptual keywords were input (beet or beetroot, nitrate or nitrite, supplement or supplementation, and exercise, efforts, and physical exercise), and covered literature from 2010 to 2019. Animal researches, review and meta-analyses articles, and inaccessible full-text, and studies that did not use beetroot juice supplementation were excluded, leaving 170 researches available. CiteSpace (version V) showed that the United States and several European countries occupied a dominant position in the carriers of beetroot juice research network. Current prominent research areas were effects of dietary NO3- supplementation, including blood pressure, O2 cost of submaximal exercise, and exercise performance. The optimal strategy for dietary NO3- supplementation and potential effects of dietary NO3- supplementation on intermittent exercise performance involve muscle fiber type recruited and the Yo-Yo intermittent recovery test..